Bifurcation diagrams in a class of Kolmogorov systems. (December 2020) - Tigan, G.; Lazureanu, C.; Munteanu, F.; Sterbeti, C.; Florea, A.
Abstract: We study a class of Kolmogorov systems of dimension two depending on two independent parameters. The local behavior of the system is described in terms of bifurcation diagrams which contain the bifurcation curves separating a node from a focus.